ANALISIS KUALITAS PELAYANAN KESEHATAN BAGI PESERTA BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN DI RS KOTA BENGKULU - Hilda Distia Puspita; Henny Aprianty; Dodo Sutardi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2019)
The main purpose of this study was to determine the quality of health care BPJS services, analyze the level of satisfaction provided by Bengkulu City Hospital. The data collection method used in this study is a descriptive qualitative approach. The techniques used in data collection are observation, interviews, and documentation. The study was conducted at Bengkulu City Hospital which began on March 20, 2018 until February 2019. The results showed that of the 5 indicators of Service Quality Dimensions of Zethalm theory, 3 showed that it was not optimal. And from 14 indicators of Community Satisfaction Dimension analysis, 7 indicators are included in the sub-optimal which need to improve quality and service.